2020
DOI: 10.34172/ajcmi.2020.15
|View full text |Cite
|
Sign up to set email alerts
|

Re-construction of Co-expression Network of Genes Involved in Bacterial Cell Wall Synthesis and Their Role in Penicillin Resistance

Abstract: Background: Peptidoglycan (Murein), which consists of disaccharide and amino acid chain subunits, has a key role in bacterial survival and ranks first in the line defense system against drug therapy. In addition, the transpeptidase enzyme plays an important role in cross-linking in bacterial cell walls. In Escherichia coli bacteria, cross-linking happens by proteins that have a D-D transpeptidase role and bond two amino acids of D-alanine together. These proteins are characterized by their affinity for and bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…In a 2018 study, multilayered carbon nanotubes showed potential synergistic effect with methicillin when treating a multi-drug-resistant Pseudomonas aeruginosa infection ( Mousavi et al, 2018 ). In a recent study, a co-expression network of genes involved in cell wall synthesis following exposure to penicillin in an Escherichia coli resistance strain has provided new targets for drug development ( Shiri et al, 2020 ). Without the continued efforts made by academic research labs, the availability of useful approaches to mitigate human susceptibility to infections caused by drug-resistant bacteria will likely remain limited.…”
Section: Discussionmentioning
confidence: 99%
“…In a 2018 study, multilayered carbon nanotubes showed potential synergistic effect with methicillin when treating a multi-drug-resistant Pseudomonas aeruginosa infection ( Mousavi et al, 2018 ). In a recent study, a co-expression network of genes involved in cell wall synthesis following exposure to penicillin in an Escherichia coli resistance strain has provided new targets for drug development ( Shiri et al, 2020 ). Without the continued efforts made by academic research labs, the availability of useful approaches to mitigate human susceptibility to infections caused by drug-resistant bacteria will likely remain limited.…”
Section: Discussionmentioning
confidence: 99%
“…A number of factors contribute to the difficulties in managing infections caused by CR-Kp, including simultaneous resistance to multiple antibiotic classes, poor patient clinical outcomes, and prolonged hospitalizations ( Vaez et al, 2019 ). Resistance to beta-lactam antibiotics, including carbapenems, is mediated by a network of different mechanisms and genes ( Dalmolin et al, 2017 ; Codjoe and Donkor, 2018 ; Shiri et al, 2020 ). The major mechanisms for carbapenem resistance in K. pneumoniae include the production of various beta-lactamases capable of hydrolyzing carbapenems as well as the reduced membrane permeability that occurs via loss or downregulation expression of outer membrane porins (OMPs) ( Dalmolin et al, 2017 ; Codjoe and Donkor, 2018 ).…”
Section: Introductionmentioning
confidence: 99%